2020
DOI: 10.1136/bmjophth-2019-000394
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of pars plana vitrectomy with subretinal tissue plasminogen activator injection and pneumatic displacement of fovea-involving submacular haemorrhage

Abstract: ObjectiveFovea-involving subretinal haemorrhage is challenging to manage with uncertain visual outcomes. We reviewed outcomes of patients with fovea-involving macular haemorrhage treated with pars plana vitrectomy (PPV) and subretinal tissue plasminogen activator (tPA) with pneumatic displacement.Methods and AnalysisThis is a retrospective interventional case series. All patients with submacular haemorrhage who underwent PPV with subretinal tPA injection were included. Reasons for exclusion encompassed patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…In 2015, Kim et al [ 16 ] reported that the most common cause of SMH in South Korea was nAMD (52.9%), followed by PCV (37.3%), RAM (5.9%), and lacquer cracks (3.9%). Other surgical studies of SMH in different geographical areas showed that the cause of SMH was nAMD in 80%–90% of cases and RAM in 5%–10% of cases [ 1 , 17 , 18 ]. In the current study, the cause of SMH was nAMD in approximately 70% of cases (tnAMD 17% and PCV 50%) and RAM in approximately 30%, and this percentage of RAM was higher than in previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, Kim et al [ 16 ] reported that the most common cause of SMH in South Korea was nAMD (52.9%), followed by PCV (37.3%), RAM (5.9%), and lacquer cracks (3.9%). Other surgical studies of SMH in different geographical areas showed that the cause of SMH was nAMD in 80%–90% of cases and RAM in 5%–10% of cases [ 1 , 17 , 18 ]. In the current study, the cause of SMH was nAMD in approximately 70% of cases (tnAMD 17% and PCV 50%) and RAM in approximately 30%, and this percentage of RAM was higher than in previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…For example, toxic effects of blood located subretinally, with early PR degeneration and subsequent cell death, have been proven. Even more, blood clots are known to produce fibrin-mediated tractional damage in different retinal layers [ 47 ]. Exudative AMD is the most frequent cause underlying SMH, but there are others such as polypoidal choroidal vasculopathy, undifferentiated and traumatic choroidal neovascularization (CNV), proliferative diabetic retinopathy and retinal arterial macroaneurysm [ 47 ].…”
Section: Indications For Subretinal Injectionsmentioning
confidence: 99%
“…Even more, blood clots are known to produce fibrin-mediated tractional damage in different retinal layers [ 47 ]. Exudative AMD is the most frequent cause underlying SMH, but there are others such as polypoidal choroidal vasculopathy, undifferentiated and traumatic choroidal neovascularization (CNV), proliferative diabetic retinopathy and retinal arterial macroaneurysm [ 47 ]. CNV can be considered the most common cause of SMH associated with AMD [ 20 ].…”
Section: Indications For Subretinal Injectionsmentioning
confidence: 99%
“…5–11 The other approach in treating SMH is PPV with subretinal rt-PA advocated as the primary treatment of choice by some authors. 12–14…”
mentioning
confidence: 99%
“…[5][6][7][8][9][10][11] The other approach in treating SMH is PPV with subretinal rt-PA advocated as the primary treatment of choice by some authors. [12][13][14] The two approaches in the management of SMH have invariably been used mutually exclusive of each other. The Manchester SMH Management Protocol is an attempt to combine the two treatment options in a more practical and pragmatic step-wise management pathway.…”
mentioning
confidence: 99%